EFFECTS OF NITROGEN SOURCE ON BIOSOLUBILIZATION OF LOW RANK COAL BY Neurospora intermedia - Wijaya, James
Although Indonesia has a lot of coal reserve, most of the coals are identified as low and medium rank coal, known to have low energy density. Therefore, a method to increase the coal energy density is required. Biosolubilization could be the solution to that problem. Biosolubilization is the process of converting solid coal to liquid coal by using biological agent at ambient conditions, which is also environmentally friendly. This research’s purpose is to determine how nitrogen source affects the quality of low rank coal biosolubilization product using Neurospora intermedia fungus. Coal mass at the end of process is used to determine biosolubilization yield. Product composition is analyzed using gas chromatography-mass spectrometry (GC-MS). Rate of biosolubilization is analyzed by the concept of turbidimetry. The nitrogen sources used for this research were ammonium nitrate and ammonium sulfate. The ratio of C/N was varied at 7, 11, and 15. The experiment was done for 14 days on a submerged culture at 30°C, 1 atm, and rotation speed of 100 rpm. According to the analysis result of humic acid and fulvic acid formation as well as the yield of biosolubilization, it is found that ammonium nitrate is a better nitrogen source than ammonium sulfate. According to the proximate analysis result, it is found that the ash content of the coal residue decreases, while the fixed carbon content increases. According to the result of product composition analysis, it is found that the number of carbon atom from the biosolubilization product ranges from 13 to 32 and that ammonium nitrate with C/N ratio of 11 is the optimal variation for coal biosolubilization.